Clusterin induced by OPC phagocytosis blocks IL-9 secretion to inhibit myelination in a model of Alzheimer's disease - Rebecca M. Beiter; Tula P. Raghavan; Olivia Suchocki; Hannah E. Ennerfelt; Courtney R. Rivet-Noor; Andrea R. Merchak; Jennifer L. Phillips; Tim Bathe; John R. Lukens; Stefan Prokop; Jeffrey L. Dupree; Alban Gaultier (Heliyon)
Background: Variants in the CLUSTERIN gene have been identified as a risk factor for late-onset Alzheimer's disease and are linked to decreased white matter integrity in healthy adults. However, the specific role for clusterin in myelin maintenance in the context of Alzheimer's disease remains unclear. Methods: We employed a combination of immunofluorescence and transmission electron microscopy techniques, primary culture of OPCs, and an animal model of Alzheimer's disease. Results: We found that phagocytosis of debris such as amyloid beta, myelin, and apoptotic cells, increases clusterin expression in oligodendrocyte progenitors. We further discovered that exposure to clusterin inhibits differentiation of oligodendrocyte progenitors. Mechanistically, clusterin blunts production of IL-9 and addition of exogenous IL-9 can rescue clusterin-inhibited myelination. Lastly, we demonstrate that clusterin deletion in mice prevents myelin loss in the 5XFAD model. Discussion: Our data suggest that clusterin could play a key role in Alzheimer's disease myelin pathology.